Peripheral blood progenitor cell (PBPC) counts during steady-state haemopoiesis enable the estimation of the yield of mobilized PBPC after granulocyte colony-stimulating factor supported cytotoxic chemotherapy: an update on 100 patients - Frühauf, Stefan; Schmitt, Karin; Veldwijk, Marlon R.; Topaly, Julian; Benner, Axel; Zeller, W. Jens; Ho, Anthony Dick; Haas, Rainer (British journal of haematology, 1999)
Peripheral blood progenitor cells (PBPC) can be mobilized using chemotherapy and granulocyte colony-stimulating factor (G-CSF). We and others previously reported a correlation of steady-state PBPC counts and the PBPC yield during mobilization in a small group of patients. Here we present data on 100 patients (patients: 25 non-Hodgkin's lymphoma (NHL), five Hodgkin's disease, 35 multiple myeloma (MM), 35 solid tumour) which enabled a detailed analysis of determinants of steady-state PBPC levels and of mobilization efficiency in patient subgroups. Previous irradiation (P = 0.0034) or previous chemotherapy in patients with haematological malignancies (P = 0.0062) led to a depletion of steady-state PB CD34+ cells. A correlation analysis showed steady-state PB CD34+ cells (all patients: r = 0.52, P < 0.0001; NHL patients, r = 0.69, P = 0.0003; MM patients: r = 0.66, P = 0.0001) and PB colony-forming cells can reliably assess the CD34+ cell yield in mobilized PB. In patients with solid tumour a similar trend was observed in mobilization after the first chemotherapy cycle (r = 0.51, P = 0.05) but not if mobilization occurred after the second or further cycle of a sequential dose-intensified G-CSF-supported chemotherapy regimen, when premobilization CD34+ counts were 18-fold elevated (P = 0.004). When the patients with MM (r = 0.63, P = 0.0008) or with NHL (r = 0.65, P = 0.006) were analysed separately, a highly significant correlation of the steady-state PB CD34+ cell count to the mean leukapheresis CD34+ cell yield was found, whereas no correlation was observed for patients with a solid tumour. For patients with haematological malignancies estimates could be calculated which, at a specific steady-state PB CD34+ cell count, could predict with a 95% probability a defined minimum progenitor cell yield. These results enable recognition of patients who mobilize PBPC poorly and may assist selection of patients for novel mobilization regimens.
Elektronische Reproduktion der Druckausgabe
Gesehen am 10.12.2021